Respiratory changes in inferior vena cava diameter versus pulse pressure variation in predicting fluid responsiveness in mechanically ventilated septic patients - Mohamed Bakry Aly; Amr Salah Ibrahim; Ayman Ibrahim Elnaggar; Mohamed Aly Hammouda (Cairo : Mohamed Bakry Aly, 2013)
Knowing whether or not a fluid infusion can improve cardiac output (fluid responsiveness) is a crucial when treating hemodynamically unstable patients. For this reason, new indices, the so-called dynamic indices of fluid responsiveness, have been recently introduced in clinical use. If stroke volume, or stroke volume derived parameters (pulse pressure and aortic flow) show wide variation during mechanical ventilation, a good response to fluid therapy can be predicted
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Inferior vena cava collapse index; Pulse pressure variations; Stroke volume variation